Tinjauan Maqasid Asy-Syariah Terhadap Program Jaminan Hari Tua - Aulia Rahman Pasaribu (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
This research aims to know review of maqasid asy-syariah through searching fund of retired plan in Indonesia. This research is included as yuridis and normative research. This research is also called as library research because this research is done by examining existing materials. Approach that used is statue approach and conceptual approach. Primary legal material which is used is government regulation number 60 year 2015 about execution of program fund of retired plan and fiqh book maqasid syariah by Yusuf Qardhawi, and seconder data, that is others literature that related to the research. The result of the research is disbursement of fund of retired plan is not accordance with initial perpose of its formation of program fund of retired plan and also not accordance with maqasid asy-syariah that is “Affirming the glory and human rights, especially the weak”, because customer is allowed to finding fund of retired plan before its time. The emphasis in maqasid asy-syariah is the weak and who is categorized as the weak is who in retirement age